Anti HSV-1 Activity of Spirulina platensis Polysaccharide - Nattayaporn Chirasuwan; Ratana Chaiklahan; Marasri Ruengjitchatchawalya; Boosya Bunnag; Morakot Tanticharoen (Agriculture and Natural Resources, 2007)
Aqueous extracts of Spirulina platensis were precipitated by cetyltrimethylammonium bromide (CTAB). The hot water extract was found anti Herpes simplex virus type 1 (HSV-1) activity at 50% inhibitory concentration (IC50) values of 21.32 μg/ml. Partial purification by gel filtration of the crude extract on Sepharose 6B column gave two fractions, SHP-F1 and SHP-F2, which revealed about 4 and 2 times higher activity than that of the crude hot water extract, respectively. The crude hot water extract was a polysaccharide with rhamnose as the main sugar component. Calcium ion and sulfate groups in this polysaccharide had major roles in antiviral activity. However, the crude hot water extract polysaccharide contained approximately 42% carbohydrate and 31% protein. Decreasing the amount of protein by precipitation with trichloroacetic acid (TCA) resulted in higher purity of the crude hot water extract polysaccharide.